Photoplethysmographic characteristics of the efficiency of the calf muscle-venous pump in norm and in patients with cvd of various clinical classes according to CEAP - E. V. Shaydakov; A. B. Sannikov (Амбулаторная хирургия)
Introduction. A literature review on the use of plethysmographic methods for studying the features of venous blood flow in lower extremities under physiological conditions and for global assessment of venous hemodynamics in chronic venous diseases urges to conduct further studies.The aim of the study was to carrying off a detailed statistical analysis of the value of the refilling time (RT) obtained during a photoplethysmographic study (PPG) to evaluate the degree of effectiveness of the calf muscle-venous pump in normal and in patients of different clinical classes according to CEAR.Materials and methods. For the period from 2002 to 2012, 116 healthy individuals with no symptoms of chronic venous diseases and 530 patients with CVD were examined with the use of PPG, with their distribution in accordance with the CEAR international classification as follows: C0-C1 – 140 people (26.42%), C2-C3 – 218 people (41.13%) and 172 persons (32.45%) had trophic disorders, that is, they belonged to the C4-C6 clinical classes. The analysis of the statistical significance of the obtained mathematical characteristics in groups by conducting a t-test for two independent samples calculated by the program and the student’s criterion Z-statistics, to conduct a correlation analysis.Results and discussion. Statistical comparative analysis of the RT value as a result of the t-test at the significance level p < 0,05 showed statistically significant differences between С0-С1, С2-С3 and С4-С6 groups with test with (or no) compression cuff. A stable correlation of average strength was observed between the groups in all cases. The differences were not statistically significant between the Norm and C0-C1 groups. The testing hypotheses for adequacy using linear regression methods allowed us to conclude that conducting a photoplethysmographic examination of patients with CVD of different clinical classes as part of the venous reflux test can provide objective information about the effectiveness of the calf muscle - venous pump. A comparative analysis in groups using the criteria RT > 20 sec and 10 < RT < 20 sec showed that there was no correlation between many groups.Conclusion. PPG is not a universal tool for diagnosing disorders of venous hemodynamics in the lower extremities. The value of RT > 20 seconds can be used as a criterion for evaluating the effectiveness of the calf muscle-venous pump, since more than 70% of cases occur in norm and in patients with C0-C1 clinical classes.